A post-Jungian perspective on the psychological development of Afrikaner cultural identity - Kotzé, Martina (Koers, 2012)
In order to enhance an understanding of different cultures and groups, post-Jungians are currently applying C.G. Jung’s theory of personal ego and complexes to the cultural level of the psyche of groups. In the post-Jungian view, much of what tears groups apart can be understood as the manifestation of autonomous processes in the collective and individual psyche that organise themselves around the cultural identity and cultural complexes of groups. A post-Jungian model of the development of the Self, based on Jung’s early identification of the archetypal patterns of Masculine and Feminine, was used to explore and discuss the development and formation of the Afrikaner cultural identity and its concomitant complexes within South Africa as they were shaped by important historical events. The interplay between the Masculine and Feminine principles led to the argument that, within the premises of the model, Afrikaner identity was forged by traumatic events in the static Feminine, which lead to a gross overemphasis of the Masculine in its dynamic and, more especially, in its static forms, reverberating in the notorious nationalist strategy of Apartheid. It was further argued that that the change and transformation of the Afrikaner cultural identity under the auspices of the dynamic Feminine was inevitable, leaving the Afrikaner in a situation in which the reconstruction of their cultural identity or identities is still emerging. It was concluded that, since all human cultures are seen as having their roots in and being centred around a religious viewpoint, as was evident in the Great Father-God, Calvinistic, patriarchal ethic of the Afrikanerdom, the individuation of the Afrikaner and the evolution of the Afrikaner cultural identity will most probably include a renewal of some of its religious viewpoints.